Peningkatan Pemahaman Fathul Kutub At Tafsir dan Hadist Berbasis Aplikasi dan Web untuk Mubaligh Muda Muhammadiyah Gedeg Mojokerto - Khoiri Khoiri; Khizanatul Hikmah; Muhlasin Amrullah (Halaqa: Islamic Education Journal, 2019)
The aim of this PPM is to improve the understanding of fathul kutub for the young muhammadiyah gedek preachers, in the form of these enhancement activities we hold a web and application based literacy training on fathul kutubtafsir wal hadis, this is because our goal is young information-friendly missionaries, but in We also give this classic literary description and the style of each book as well as the steps to open it, so that it is not only friendly with applications, but the young preachers also pay attention to classical textbooks, this is very important for the preachers, by increasing literacy and scientific passion and insight the preacher will develop as well as what is conveyed to the community contains elements of knowledge and is protected from hoaxes.